Constitutive parameter analysis of left-handed dual-star split-ring resonator metamaterial for homogeneous infinite slab - Ullah, M.H.; Uddin, M.J.; Latef, T.A.; Mahadi, W.N.L.; Ahsan, M.R.; Islam, M.T. (2015)
A new shaped backward wave periodic dual-star split-ring resonator (DSSRR) is proposed based on the equivalent transmission line theory. The proposed artificial DSSRR design structure produces a wide band from 7.5 to 9.5 GHz, and very high rejection (47 dB) with sharp cut-offs in the forbidden band. To ensure the retrieval of electromagnetic parameters, primarily a single unit cell is considered. Then, the periodic four unit cells are decomposed to investigate the excitation metamaterial properties. The constitutive properties of the dispersion diagram exhibited very unusual characteristics and separated into different directions in balanced and unbalanced conditions in order to excite propagation in different modes. The dispersion of left-handedness group velocity exhibits the parallel direction of the poynting vector and high gain in higher frequency regions, whereas the phase velocity demonstrates the anti-parallel direction of the poynting vector obtained from the resonance frequency regions. The overall electromagnetic parameters of negative dielectric constant, resonance permeability, anti-parallel phase and group velocity, and refractive index confirm that the proposed periodic DSSRR artificial structure to be the most suitable for metamaterial behaviour and characteristics.